2022
DOI: 10.3390/en15092988
|View full text |Cite
|
Sign up to set email alerts
|

Emission and Performance Evaluation of a Diesel Engine Using Addition of Ethanol to Diesel/Biodiesel Fuel Blend

Abstract: Many countries have adopted the addition of biodiesel to diesel as a way of inserting renewable content into mineral fuel and making a contribution to the environment. The addition of ethanol to the diesel/biodiesel blend to increase the renewable content of the added fuel blend and reduce the percentage of biodiesel could be a strategysince the demand for biodiesel production is high, and this fuel has a high production cost when compared to ethanol. Thus, this study evaluated the performance and the content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
(73 reference statements)
1
11
0
Order By: Relevance
“…NO x emissions are the primary pollutants emitted during the combustion of fuel in diesel engines, and NO x causes climatic impacts as well as health concerns . NO x emissions are influenced by various factors of the fuel, including the air–fuel interaction in combustion, the combustion temperature in the cylinder, residence time, density, cetane number, and oxygen content. ,, Figure b shows the NO x emissions for diesel, RCPOM, and fuel blends at various engine speeds and loads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO x emissions are the primary pollutants emitted during the combustion of fuel in diesel engines, and NO x causes climatic impacts as well as health concerns . NO x emissions are influenced by various factors of the fuel, including the air–fuel interaction in combustion, the combustion temperature in the cylinder, residence time, density, cetane number, and oxygen content. ,, Figure b shows the NO x emissions for diesel, RCPOM, and fuel blends at various engine speeds and loads.…”
Section: Resultsmentioning
confidence: 99%
“…Krishna et al, 29 Kaulani et al, 31 and de Oliveira et al 33 reported that increasing the concentration of ethanol in the fuel decreased BTE and increased BSFC for a maximum ethanol content of 15% when compared to diesel. Freitas et al 34 found that adding 10% ethanol to a diesel−biodiesel−ethanol blend reduced torque and brake power (P b ) by 6%. However, the thermal efficiency of each fuel was not considerably different.…”
Section: Introductionmentioning
confidence: 99%
“…This work focuses on one speed (1500 rpm) because a relatively high torque of a similar mechanical diesel engine was obtained for diesel/ethanol blends at this speed (Freitas et al, 2022). 4.1 Brake Power of diesel engine Figure 4 shows the brake power of engine and torque of the tested diesel engine using diesel and modified diesohol (D85E15G1.2DT-C1).…”
Section: Engine Performance Testmentioning
confidence: 99%
“…Another method used to reduce exhaust emissions is the use of various alternative fuels to power engines. Currently, the most studied alternative fuels for compression ignition engines are biodiesel, vegetable oils, alcohols, dimethyl ether, dimethyl carbonate, natural gas, liquefied petroleum gas, methane, methane, propane, hydrogen and waste materials [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Some of these alternative fuels can be used in pure form while others are used as dual fuels, fuel blends and emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Freitas et al [45] evaluated the performance and NO x , CO, and CO 2 content of a compression-ignition engine fueled with three blends of diesel, biodiesel, and ethanol: pure B7, B7E3 (B7 with 3% ethanol), and B7E10 (B7 with 10% ethanol). The experimental studies were performed for fixed engine speeds in the range of n = 1000-1750 rpm and for fixed loads in the range of 10-100% of maximum torque.…”
Section: Introductionmentioning
confidence: 99%